Frontispiece: Efficient Inhibition of SARS‐CoV‐2 Using Chimeric Antisense Oligonucleotides through RNase L Activation. Issue 40 (20th September 2021) - Su, Xiaoxuan; Ma, Wenxiao; Feng, Di; Cheng, Boyang; Wang, Qian; Guo, Zefeng; Zhou, Demin; Tang, Xinjing
Abstract : SARS‐CoV‐2 In their Communication on page 21662, Xinjing Tang et al. report the efficient inhibition of SARS‐CoV‐2 using chimeric antisense oligonucleotides through RNase L activation.